Pengembangan Sistem Informasi Persediaan Barang Menggunakan Model Waterfall untuk Meningkatkan Efisiensi Pengelolaan Stok - Fathoni, Muhammad; kustiyono (Institut Teknologi Garut, 2025)
This study addresses stock-management challenges at Toko Sinar Mulia, where inventory processes are still performed manually and are prone to errors, by designing a web-based inventory system using the Laravel framework. Adopting the Waterfall model within the Software Development Life Cycle (SDLC), the information system aims to improve the efficiency and accuracy of stock recording and management. The main contribution of this research is providing a structured solution for digitizing inventory management, which previously lacked automation, thereby supporting more effective decision-making and store operations.